Factors associated with food choices among elderly: a scoping review - Mohd Shahrin, Fatin Izzaty; Omar, Noraida; Mat Daud, Zulfitri ‘Azuan; Zakaria, Nor Fadhlina (Nutrition Society of Malaysia, 2019)
Introduction: The aging population is a matter of global concern. Age-related physiological, pathological, psychosocial, economic, cultural and environmental changes are common and may greatly influence the quality of life of the elderly. The aim of this review was to explore the determinants and motivations that drive the elderly in making food choices. Methods: The search strategy of this literature review used the PRISMA protocol. Potential literature that was related to food choices was identified using two different combinations of keywords and two major electronic search engines, namely Pubmed and Science Direct. The articles that were selected for this review had to be in the English language, open-accessed and published between January 2007 and December 2017. Results: From a search of 1398 articles, 15 articles (seven quantitative and eight qualitative) were identified that were related to food choices among the elderly. The key factor that determined food choices among the elderly population was identified to be health. Others included convenience, sensory appeal, price, early food experience and more. The limitations of these studies that were reported were the small sample size and the reliance on self-reporting. The conclusions that were drawn were for specific groups that were studied in this review should be extrapolated or generalised with caution. Conclusion: Strategies for intervention programmes should be undertaken in collaboration with health professionals, researchers, policymakers, and the food industry. Future research is needed in the elderly who have chronic diseases, are dependent or who have disabilities.